2003
DOI: 10.1016/j.physletb.2003.06.050
|View full text |Cite
|
Sign up to set email alerts
|

A new state of baryonium

Abstract: The recent discovery of a narrow resonance in the decay J/ψ → γpp is described as a zero baryon number, deuteron-like singlet 1 S 0 state. The difference in binding energy of the deuteron (−2.225 MeV) and of the new state (−17.5 MeV) can be accounted for in a simple potential model with a λ · λ confining interaction.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
102
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 26 publications
0
102
0
2
Order By: Relevance
“…Since this enhancement structure is close to the pp threshold, the X(1835) was suggested to be a baryonium state in Refs. [194,195,196].…”
Section: +5mentioning
confidence: 99%
“…Since this enhancement structure is close to the pp threshold, the X(1835) was suggested to be a baryonium state in Refs. [194,195,196].…”
Section: +5mentioning
confidence: 99%
“…On the theoretical side this discovery has been discussed by several authors [4,5,6,7]. In [4] the near-threshold effect has been considered either as a gluonic state or as a result of the quark fragmentation process.…”
mentioning
confidence: 99%
“…An interesting feature of this enhancement is that corresponding structures are not observed in near-threshold pp cross section measurements, or in B-meson decays [2], or in radiative ψ [3] or ϒ → γ pp decays [4], or in J/ψ → ω pp decays [5]. One of theoretical speculations [6] is the intriguing suggestion that it is a pp bound state, sometimes called baryonium [6]. It also stimulated a study of J/ψ → γπ + π − η , in which a resonance, the X(1835), was observed in the π + π − η invariant-mass spectrum with a statistical significance of 7.7σ at BESII [7].…”
Section: Introductionmentioning
confidence: 99%
“…It also stimulated a study of J/ψ → γπ + π − η , in which a resonance, the X(1835), was observed in the π + π − η invariant-mass spectrum with a statistical significance of 7.7σ at BESII [7]. The possible interpretations include a pp bound state [6], a glueball [8], a radial excitation of the η meson [9], etc.…”
Section: Introductionmentioning
confidence: 99%